Delitos, violencias y escándalos sexuales en Chile: escalas de análisis metodológico (fines siglo XVIII - mediados siglo XIX) - Nicolás Celis Valderrama (Nuevo mundo - Mundos Nuevos, 2018)
This article is a methodological reflection that arises from the review of a documentary body constituted by judicial files that address sexual crimes from the end of the 18th century until the middle of the 19th century. These files come from courts throughout the Chilean territory and address matters relating to rape, abduction, rape and incest. Without dodging some theoretical approaches, violence and scandal, the core will be limited to the proposal of five scales of methodological analysis to address sexual crimes, applied to a judicial file for rape of 1784. The files for sexual crimes not only allow visibility and to put in historical perspective the magnitude of the violence carried out by the aggressors on the victims, but also a relation of power and authority exerted by the first on the second ones and of subjection of these. Finally, from its records it is possible to notice that the actors involved report, more than sexual aggression, violence or abuse, the seriousness of these acts, because these have exceeded the limit of what is tolerated.